Student’s Perception of Syllabus Adoption in Higher Education; Redesigning for the Age of AI - Tlalane Mosae; Rekha Kaushal (Journal of Research in Education and Pedagogy, 2025)
This research investigates the incorporation of artificial intelligence (AI) within higher education curricula, concentrating on students’ views regarding necessary syllabus modifications to adequately prepare for a future influenced by AI. The study delineates three primary objectives: to determine what elements should be included in the syllabus, to identify key AI tools for academic growth, and to understand the challenges associated with embedding AI into current educational frameworks. A qualitative research study was adopted, employing semi-structured interviews with ten students selected through purposive sampling. A thematic analysis was performed to uncover recurring themes and insights. The results reveal a significant demand for AI literacy, project-based learning, and practical applications as vital components of a restructured syllabus. Students identified tools such as Grammarly, ChatGPT, and specialized AI platforms for various disciplines as essential for academic achievement. Nonetheless, the challenges of over-reliance on AI, diminished creativity, and complacency were also noted. This investigation highlights the necessity for a syllabus that effectively balances technological integration with the maintenance of creativity and critical thinking. By considering student perspectives, higher education institutions can enhance readiness for graduates poised to enter an AI-influenced job market. The implications of this study suggest that educators should emphasize the inclusion of project-based learning modules that motivate students to leverage AI tools for addressing real-world challenges. Faculty development programs should aim at providing educators with the competencies required to assist students in the ethical and productive application of AI. Future inquiries should examine faculty opinions and the long-term effects of AI-enhanced syllabi.